Logan's turbomachinery : flowpath design and performance fundamentals - Sultanian, Bijay K.; Logan, Earl. (Boca Raton : CRC Press, Taylor & Francis Group, 2019)
Logan's Turbomachinery: Flowpath Design and Performance Fundamentals, Third Edition is the long-awaited revision of this classic textbook, thoroughly updated by Dr. Bijay Sultanian. While the basic concepts remain constant, turbomachinery design has advanced since the Second Edition was published in 1993. Airfoils in modern turbomachines feature three-dimensional geometries, Computational Fluid Mechanics (CFD) has become a standard design tool, and major advances have been made in the materials and manufacturing technologies that affect turbomachinery design. The new edition adresses these trends to best serve today's students, and design engineers working in turbomachinery industries.
Revised edition of: Turbomachinery.
OCLC-licensed vendor bibliographic record.
Keywords: Turbomachines; TECHNOLOGY & ENGINEERING / Mechanical; SCIENCE / Energy; SCIENCE / Mechanics / Dynamics / Thermodynamics; TECHNOLOGY / Engineering / Mechanical